Exploring the Meaning of Addressing Ité in the Manggarai Language and Culture - Menggo, Sebastianus; Ndiung, Sabina (Bina Nusantara University, 2024)
The research explored the connection between the linguistic elements and cultural principles of the Manggarai language, focusing on the provided arguments. Language utilization typically represented the societal customs, cognitive processes, cognitive functioning, historical context, and interconnections within a given human civilization. Utilizing the inclusive personal pronoun, ‘we ité’ in the Manggarai language facilitated the identification of two indicated elements (linguistic elements and cultural principles). The research applied a descriptive-qualitative method. Data were obtained using observations and interviews conducted with fifteen traditional representatives from six communities using the purposive sampling method. Subsequently, a qualitative analysis was performed on the collected data. The findings suggest that its utilization in its various manifestations indicates the cultural norms and customs observed by those living in the Manggarai region of Indonesia. Based on the presented data, the research asserts that the first personal pronoun plural inclusive ‘we ité’ in the Manggarai language and culture serves as a means for the speaker to communicate politeness and humility towards the hearer or listener. It signifies a genuine respect for the interlocutor, particularly when they hold a high position. In addition, it shows familiarity, brotherhood, and sincerity in interpersonal relationships by expressing respect, appreciation, and enthusiasm. Lastly, it serves as a profound respect to the Almighty Creator.